2015
DOI: 10.2147/opth.s80500
|View full text |Cite
|
Sign up to set email alerts
|

Real-world assessment of intravitreal dexamethasone implant (0.7 mg) in patients with macular edema: the CHROME study

Abstract: BackgroundThe purpose of this study was to evaluate the real-world use, efficacy, and safety of one or more dexamethasone intravitreal implant(s) 0.7 mg (DEX implant) in patients with macular edema (ME).MethodsThis was a retrospective cohort study of patients with ME secondary to retinal disease treated at ten Canadian retina practices, including one uveitis center. Best-corrected visual acuity (BCVA), central retinal thickness (CRT), intraocular pressure (IOP), glaucoma and cataract surgery, and safety data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 27 publications
5
60
0
1
Order By: Relevance
“…18 Another study reported that the improvements in BCVA and central retinal thickness at 1 month were similar (not significantly different) following the first and second implants. 84 In a study of uveitis patients the median time from first to second implant was 10 months 50 whereas in four studies of uveitic macular oedema the mean/median time from first to second implant was 4.7, 81 5.0, 51 7.1 83 and 10 86 months. The mean time from second to third implant was 3.4 months in one study of uveitic macular oedema.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Another study reported that the improvements in BCVA and central retinal thickness at 1 month were similar (not significantly different) following the first and second implants. 84 In a study of uveitis patients the median time from first to second implant was 10 months 50 whereas in four studies of uveitic macular oedema the mean/median time from first to second implant was 4.7, 81 5.0, 51 7.1 83 and 10 86 months. The mean time from second to third implant was 3.4 months in one study of uveitic macular oedema.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
“…18,50,51,[79][80][81][82][83][84][85][86] This is based on data from the company submission for DEX; 43 the original study publications have not been examined because of time constraints. These data are included here as they provide some data on repeat implants, implants in both eyes and corticosteroid reduction, which were not assessed in the HURON trial.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these implants have the potential to reduce the costs and overall treatment burden associated with other therapies [14]. Although an intravitreal dexamethasone implant (Ozurdex at a dose of 0.7 mg; Allergan Inc., Irvine, CA, USA) has been available in Brazil since 2012, unlike other countries [15-20] no clinical studies have been reported thus far assessing the use of this product specifically in the treatment of DME. We aimed to assess the real-world use of this product in order to further characterize its effectiveness and safety among patients with DME treated in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…Aflibercept (Eylea®; Regeneron Pharmaceuticals, Inc., Tarrytown, NY, USA) was approved for CRVO in September 2012 and for BRVO in 2014. [13,14]…”
Section: Introductionmentioning
confidence: 99%